(untitled) (Journal of the College of Basic Education, 2023)
There are many requirements to achieve the athletic accomplishment such as the physical and skillful characteristics and psychological abilities. There are many aspects of the psychological abilities and amongst which is attention whose most important aspects are intensity, concentration and conversion that have a vital role in the carrying out the forehand and backhand strokes in badminton.The importance of the study lies in studying the intensity, concentration and the conversion of attention and their relationship with the two skills of the front and rear strokes in badminton.The researcher has studied and investigated the psychological aspects of this problem which are not less important than the other aspects. It is to be noted that there are many scientific research articles that tackle the physical and functional aspects whereas the psychological aspect has not been paid concern, study and research.The study aims at:1. Identifying some of the manifestations of attention (intensity, concentration and conversion of attention) of the Iraqi junior badminton player.2. Identifying the two skills of the forehand and backhand strokes of the Iraqi junior badminton player.3. Identifying the relationship between some of the manifestations of attention (intensity, concentration and conversion of attention) and the forehand and backhand strokes of the Iraqi junior badminton player.The research sample has been represented by (38) players who represent the junior players participating in the Iraq Open Badminton Championship and who have been selected by the intentional method.Then, the researcher has processed the data statically and reached a number of conclusions as shown below:1. There is correlation between the intensity of attention and the skills of doing the forehand and backhand strokes in badminton.2. There is correlation between the concentration of attention and the skills of doing the forehand and backhand strokes in badminton.3. There is correlation between the conversion of attention and the skills of doing the forehand and backhand strokes in badminton.As to recommendations, they have been as follows:1. Concern should be paid to a good psychological preparation in training and in contests besides the physical and the skillful preparation in badminton.2. Concern should be paid by coaches to set up training programs to attention and develop the intensity, concentration and conversion of attention which is an important factor to raise badminton players’ level.3. Training courses in the field of sports psychology should be conducted to explain the effect of the psychological condition on performance